1991
DOI: 10.1017/s0033291700014781
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing compulsory admission of psychiatric patients

Abstract: SYNOPSISFrom 1 January 1984 until 30 June 1986 all 517 compulsorily admitted psychiatric patients of a well-defined mixed rural–urban catchment area in Baden-Württemberg, a southern State of the German Federal Republic, were compared with all 10232 voluntarily admitted patients. Because of the very low frequency of compulsory admissions this population can be regarded as a ‘core group’ of committed patients. In a logit analysis the characteristics distinguishing involuntary from voluntary patients can be reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
3
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 37 publications
7
38
3
2
Order By: Relevance
“…We selected these variables, because previous studies have shown their association with either mortality or compulsory treatment. [14][15][16][17][18] We regarded cases and controls as independent, because there was no reason to believe that their outcomes were correlated in any way. 19 We initially examined associations using unadjusted odds ratios (ORs).…”
Section: Discussionmentioning
confidence: 99%
“…We selected these variables, because previous studies have shown their association with either mortality or compulsory treatment. [14][15][16][17][18] We regarded cases and controls as independent, because there was no reason to believe that their outcomes were correlated in any way. 19 We initially examined associations using unadjusted odds ratios (ORs).…”
Section: Discussionmentioning
confidence: 99%
“…However, in their review of international studies investigating influential factors in compulsory admission of psychiatric patients, Riecher et al, (1991) highlight the need for care in interpreting risk of harm to self and others. Countries with lower legislative thresholds for compulsory admission appear to have people more 'dangerous to themselves or others' than with slightly less restrictive systems (p. 198).…”
Section: Discussionmentioning
confidence: 99%
“…Such factors may include the characteristics of the illness itself-the symptoms and their severity-the availability of family and social support, the physical environment of the individual and the attributes of the mental health professionals responsible for their treatment (Riecher et al, 1991;Srikumar & Orrell, 1995). Case note studies indicate that age is also an important factor in the process.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, the percentage of immigrant patients involuntarily admitted to a psychiatric intensive unit varies considerably among the different hospitals (Bjorngaard & Heggestad 2001). The different clinical characteristics of patients, such as gender, diagnosis and age, have been associated with the use of coercion and involuntary admissions (Riecher et al . 1991, Bjorngaard & Heggestad 2001).…”
Section: Introductionmentioning
confidence: 99%